Channels to shape procurement decision-making of public organisations for innovation through framework conditions. (4th February 2022) - Liu, Jing; Kang, Xiaoling; Zhang, Xia; Chen, Xing
Abstract: Framework conditions (FCs) are widely recognised as having a significant effect on the uptake and implementation of innovation-orientated public procurement (PPI) that is viewed as a promising innovation policy instrument. This paper presents a more systemic definition of FCs for PPI at both the core and the peripheral level, building on the existing understanding of FCs for public procurement and innovation. Against the background of this definition and in the light of public organisation theory, this paper identifies three main channels—influencing performance (Channel 1), enhancing capabilities (Channel 2), and modifying missions (Channel 3)—to shape purchase decision-making of public organisations for innovation through the FCs. By comparing the case of the UK and China, it further explores and conceptualises the three channels of the FCs. With the conceptualisation, the paper provides a framework and some implications for how to design, improve and evaluate FCs for PPI.